Carceral con: the deceptive terrain of criminal justice reform - Whitlock, Kay (University of California Press, 2021)
Introduction : world-making and "criminal justice reform" -- Correctional control and the challenge of reform -- Follow the money -- Criminalization, policing, and profiling -- The slippery slope of pretrial reform -- Courts, sentencing, and "diversion" -- Imprisonment and release -- Threshold.